2005
DOI: 10.1080/00016480510026908
|View full text |Cite
|
Sign up to set email alerts
|

A new translational platform for evaluating aging or pathology-related postural disorders

Abstract: The translational platform, the new parameters elaborated for quantifying postural reactions (energy and time for postural stabilization, phase and gain of the postural response) and the visual condition under which the subjects were tested (eyes open versus eyes closed) discriminated all groups better than the classical methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 21 publications
1
21
0
1
Order By: Relevance
“…In particular, important information on the dynamic of the CoP may be reached by applying nonlinear analysis methods such as the wavelet transformation method. Indeed, a study by Ghulyan et al (2005) demonstrated that a dynamic analysis of posture allows a better discrimination of the pathological effects on postural control.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, important information on the dynamic of the CoP may be reached by applying nonlinear analysis methods such as the wavelet transformation method. Indeed, a study by Ghulyan et al (2005) demonstrated that a dynamic analysis of posture allows a better discrimination of the pathological effects on postural control.…”
Section: Introductionmentioning
confidence: 99%
“…Such analysis reveals effects in the dynamics of the postural control system that are not shown by the more traditional posturography method based on spatial analysis only. A study by Ghulyan et al (2005) has demonstrated that dynamic postural analysis allowed a better discrimination of age effect on posture. Moreover, Lacour et al (2008) have described the limits of the traditional static posturography method, suggesting that the spatial analysis of the center of pressure could lead to misevaluations of the balance control system.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have proposed that evaluating postural control in challenging postures, instead of during a simple “standing upright” condition, may be necessary to detect alterations of postural control (e.g. [34], [48]). This point was beyond our aim, i.e.…”
Section: Discussionmentioning
confidence: 99%